2010
DOI: 10.1186/1755-8794-3-46
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine gene expression in lung CD8 T cells correlates with protective immunity in mice immunized intra-nasally with Adenovirus-85A

Abstract: BackgroundImmunization of BALB/c mice with a recombinant adenovirus expressing Mycobacterium tuberculosis (M. tuberculosis) antigen 85A (Ad85A) protects against aerosol challenge with M. tuberculosis only when it is administered intra-nasally (i.n.). Immunization with Ad85A induces a lung-resident population of activated CD8 T cells that is antigen dependent, highly activated and mediates protection by early inhibition of M. tuberculosis growth. In order to determine why the i.n. route is so effective compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…While not yet evaluated, it is also possible that chemokine production is dysregulated in influenza-specific effector cells. CD8 + T cells can produce a number of chemokines that regulate the recruitment and function of a broad array of cells (53, 54). In disease processes where individuals survive past the initial phase of bacterial infection (24–48h), as is the case in our model, a reduction in cytokines/chemokines has the potential to significantly impact ongoing inflammation and/or the response to tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…While not yet evaluated, it is also possible that chemokine production is dysregulated in influenza-specific effector cells. CD8 + T cells can produce a number of chemokines that regulate the recruitment and function of a broad array of cells (53, 54). In disease processes where individuals survive past the initial phase of bacterial infection (24–48h), as is the case in our model, a reduction in cytokines/chemokines has the potential to significantly impact ongoing inflammation and/or the response to tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…immunization with Ad85A. BALB/c mice immunized with Ad85A i.n., but not i.d., showed a statistically significant reduction in mycobacterial load following pulmonary M. tuberculosis challenge (Table 1) (26,40). Since microarray analysis of CD8 T cells isolated from the lungs of mice immunized with Ad85A i.n.…”
Section: Resultsmentioning
confidence: 99%
“…immunized mice showed enhanced expression of several tissue-targeting chemokines and a single chemokine receptor, CXCR6, compared to lung CD8 T cells from i.d. immunized mice (26).…”
mentioning
confidence: 99%
“…It has also been reported that CXCR6 + memory CD8 + T cells accumulate in the lung following intranasal, but not intradermal delivery of antigen (72,73). In fact, the expression of CXCL16 is strongly enhanced in response to inflammatory stimuli, thereby accelerating the active re-cruitment of effector T cells into inflamed tissues (2,38,85).…”
Section: Takamuramentioning
confidence: 99%